2011
DOI: 10.1093/jac/dkq539
|View full text |Cite
|
Sign up to set email alerts
|

Extensive dissemination of CTX-M-producing Escherichia coli with multidrug resistance to 'critically important' antibiotics among food animals in Hong Kong, 2008-10

Abstract: This study shows that food animals are a major reservoir of E. coli with multidrug resistance to many antibiotics that are ranked as critically important in human medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
78
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(93 citation statements)
references
References 7 publications
13
78
2
Order By: Relevance
“…A number of investigations have been conducted in various parts of the world to investigate the presence and types of ESBL in cattle [8][9][10][11][12][31][32][33], but research on ESBL in sheep is limited [8,11,33]. In Turkey, only one study has been conducted so far in which both the presence and types of ESBLs in cattle and sheep were investigated, and this was in the northwest of Turkey [15].…”
Section: Discussionmentioning
confidence: 99%
“…A number of investigations have been conducted in various parts of the world to investigate the presence and types of ESBL in cattle [8][9][10][11][12][31][32][33], but research on ESBL in sheep is limited [8,11,33]. In Turkey, only one study has been conducted so far in which both the presence and types of ESBLs in cattle and sheep were investigated, and this was in the northwest of Turkey [15].…”
Section: Discussionmentioning
confidence: 99%
“…It should be pointed out that live poultry are sold in wet markets in 16 of the 18 districts. Our previous work found that ESBL-producing E. coli was carried by eight out of ten live poultry (Ho et al, 2011a). It is possible that better access of some rodents to faecal materials of food animals might have contributed to the variation in resistance rates.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies assessed changes in human population density over ranges of ,1 km 22 , ,50 km 22 and 200 km 22 (Skurnik et al, 2006), while the 18 districts in the present study had densities from 800-55200 km 22 . Besides sewage, variations in resistance rates may be explained by other possibilities such as better access of some rats to farms, wet markets, grocery stores, hospitals, human food sources and garbage disposal areas (Guenther et al, 2013;Ho et al, 2011a;Kola et al, 2012). In Hong Kong, farms producing food animals (poultry and pigs) are almost exclusively located in the Yuen Long district (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations